Enterobacteriaceae resistentes às cefalosporinas de terceira geração isoladas em amostras obtidas nas primeiras 48 horas de internação em um hospital geral: frequência, fatores de risco e impactos na evolução clínica - Mirian Cristina de Oliveira (2013)
Enterobacteriaceae are the most frequently pathogens isolated from clinical specimens. Third generation cephalosporins and fluoroquinolones constitute the main therapeutic choices for infections caused by these microorganisms. Although the infections caused by ESBL and AmpC-producing Enterobacteriaceae are commonly seen among in-hospital patients, during the last years, these organisms have been increasingly reported in the community and health care-associated infections. This study aimed at evaluating the frequency, risk factors and clinical impact of third generation-resistant Enterobacteriaceae isolated in samples collected within 48 hours following hospital admission. By using an observational, prospective, controlled design, all adult patients (age 18 years) in whom were isolated Enterobacteriaceae in samples collected within 48 hours following the admission at the University Hospital of the Universidade Federal de Minas Gerais, during August 2011 to July 2012 were considered for potential inclusion. Of the 238 patients with isolated within the first 48 hours, 62 (26.05%) were colonized or infected with resistant Enterobacteriaceae to third-generation cephalosporins (Case Group), and 176 (73.95%) were colonized or infected with susceptible Enterobacteriaceae to third-generation cephalosporins. For each case, two controls with susceptible Enterobacteriaceae were selected sequentially at the same day (Control Group), totalizing 124 controls. Considering all patients, there was a predominance of females, and the mean age was 50.2 years (± 19.98 years). In a multivariate analysis, male gender (OR, 2.56; CI 95%, 1.19 5.47, P=0.016), presence of stoma (OR, 5.09; CI 95%, 1.46-17.75; P=0.010), and previous hospitalization in the past 6 months (OR, 5.16; CI 95%, 2.43-10.97; P< 0.001) were independent risk factors for infection due to Enterobacteriaceae resistant to third generation cephalosporins. Infection caused by these microorganisms was associated with higher frequency of inappropriate empirical therapy (73,3% vs. 10,3%, P<0,001), worse clinical outcomes, as increased frequency of admission in ICU or Emergency Room (44.1% vs. 22.6%, P=0.003), lower incidence of partial or complete resolution of infection (63.3% vs. 79.1%, P=0.049) and longer hospital stays (13 days vs. 5 days, P<0,001). Considering the independent risk factors, a score was calculated. We observed that the probability of isolating resistant enterobacteria increased in proportion to the values of the score, from 26.1% for 1point to 93.5% for 5 points. In conclusion, we observed a high frequency of Enterobacteriaceae resistant to third-generation cephalosporins were isolated at the hospital admission. Considering the risk factors identified in this study, and the harmful clinical consequences of these microorganisms, the protocols of empiric antibiotic therapy for patients with serious infections should be reviewed.